Endodontics pastes formulated with copaiba oil: action on oral microbiota and dentin bridge formation in dogs - Dias, Fernanda Gosuen Gonçalves; Casemiro, Luciana Assirati; Martins, Carlos Henrique Gomes; Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Pereira, Lucas De Freitas; Nishimura, Lilian Toshiko; Souza, Fabiana Ferreira De [UNESP]; Honsho, Cristiane Dos Santos (Universidade Federal de Santa Maria, 2015)
This study analysed the effect of pastes formulated with calcium hydroxide P.A. and different vehicles (saline solution - paste A and Copaifera langsdorffii Desfon oil - paste B) on oral microorganisms and dentin bridge formation in dogs. The antimicrobial action of the pastes and their components was analysed by the minimum inhibitory concentration in agar gel technique. The components were diluted and tested on fifteen standard strains of microorganisms associated with endodontic diseases. The microorganisms were cultivated and after incubation data was analysed using One-Way ANOVA and Turkey's test (P≤0.05). Four superior incisors of ten animals were used to evaluate dentin bridge formation. Two incisors were capped with paste A (GA) and two with paste B (GB). After 90 days, the teeth were extracted for histological analysis and the degree of dentin bridge formation evaluated. Data was analysed by the Kruskal-Wallis test (P<0.05). The pastes and their components were classified in the following decreasing order of antimicrobial action: calcium hydroxide P.A., paste A, paste B and Copaifera langsdorffii Desfon oil. Calcium hydroxide P.A. showed significantly higher antimicrobial action than the pastes or their vehicles. No significant difference was observed between the two pastes in dentin bridge formation. Based on the microorganisms studied, it can be concluded that the pastes analysed showed similar antimicrobial potential but differed significantly from their individual components. No significant difference was observed in dentin bridge formation between the different pastes tested.

Foi avaliada a ação de pastas formuladas com hidróxido de cálcio P.A. e diferentes veículos (solução fisiológica - pasta A e óleo de Copaifera langsdorffii Desfon - pasta B) sobre microrganismos bucais e formação de ponte dentinária em cães. A ação antimicrobiana das pastas e de seus componentes individuais foi avaliada pela técnica da concentração inibitória mínima pela diluição em ágar. Os materiais foram diluídos e avaliados contra quinze cepas padrão de microrganismos relacionados a doenças endodônticas. Os microrganismos foram cultivados e, após a incubação, os dados foram analisados (Anova One-Way, Tukey, P≤0,05). Para a avaliação da formação de ponte dentinária, quatro incisivos superiores de dez animais foram tratados, sendo dois capeados com pasta A (GA) e dois com a pasta B (GB). Após 90 dias, os dentes foram extraídos para obtenção de cortes histológicos, com o objetivo de se avaliar o grau de formação de ponte dentinária. Os dados obtidos foram submetidos à análise estatística (Kruskal-Wallis, P<0,05). Segundo a ação antimicrobiana, os materiais foram classificados em ordem decrescente: hidróxido de cálcio P.A., pasta A, pasta B e óleo de Copaifera langsdorffii Desfon, com diferenças estatisticamente significantes entre o hidróxido de cálcio P.A., as pastas e os veículos. Ao final do estudo, observou-se que as duas pastas avaliadas foram semelhantes quanto à formação de ponte dentinária. Considerando-se os microrganismos selecionados, conclui-se que as pastas avaliadas foram semelhantes entre si em termos de potencial antimicrobiano, diferindo dos componentes individuais. Em relação à formação de ponte dentinária, não foram observadas diferenças significantes entre os dentes tratados com as diferentes pastas.
Pastas endodônticas formuladas com óleo de copaíba: ação na microbiota bucal e formação de ponte dentinária em cães
Keywords: Microbiology; Dental pulp capping; Medicinal plants; Microbiologia; Capeamento da polpa dentária; Plantas medicinais